Fiber-reinforced metal composite material and preparation method thereof

By pretreatment and surface treatment of fiber and metal matrix, combined with hot pressing and annealing treatment, the problems of insufficient bonding force and uneven fiber distribution are solved, and the mechanical properties and stability of composite materials are significantly improved .

CN119426563AInactive Publication Date: 2025-02-14BEIJING PENGYUAN NEW MATERIALS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411626857.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In traditional fiber-reinforced metal composite materials, the interface bonding force between the fiber and the metal matrix is ​​insufficient, resulting in the material being prone to interface failure under the action of external forces, and the fiber distribution is uneven, affecting the consistency and reliability of the material.

Method used

The interface bonding force between the fiber and the metal matrix is ​​improved by pretreating and surface treatments such as electroless plating, surface oxidation and plasma treatment. At the same time, thermal press forming and annealing treatment are used to ensure the uniform distribution of fibers in the metal matrix and the optimization of the microstructure of the material.

Benefits of technology

It significantly improves the tensile strength and fracture toughness of the composite material, ensures the uniform distribution of fibers in the matrix, reduces the local performance differences of the material, and improves the stability and service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119426563A_ABST
    Figure CN119426563A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of composite materials, and discloses a fiber-reinforced metal composite material and a preparation method thereof.The composite material comprises a metal matrix, the metal matrix is selected from aluminum alloy, titanium alloy, magnesium alloy and nickel-based alloy, and the metal matrix is pretreated to improve combination of the metal matrix and fibers; the high-strength fibers are subjected to surface treatment, the surface treatment comprises but is not limited to chemical plating, coating or plasma treatment, the high-strength fibers are selected from carbon fibers, boron fibers, glass fibers or a combination of the carbon fibers, the boron fibers and the glass fibers, and the high-strength fibers are uniformly distributed in the metal matrix to form a multi-scale reinforced structure; according to the invention, through surface treatment and proper pretreatment means, the interface bonding force between the fiber and the metal matrix is obviously enhanced, so that the tensile strength and fracture toughness of the composite material are improved. And a transverse vibration technology is adopted, so that uniform distribution of fibers in a metal matrix is effectively promoted, and the phenomenon of non-uniform performance caused by fiber aggregation is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite materials, in particular to a fiber-reinforced metal composite material and a preparation method thereof. Background Art

[0002] Fiber-reinforced metal composites are an important high-performance material widely used in aerospace, automobile manufacturing, sports equipment and other fields. This type of composite material improves its mechanical properties, such as tensile strength and fracture toughness, by introducing high-strength fibers into the metal matrix. In order to further improve the performance of the composite material, it is usually necessary to pretreat the fiber and metal matrix, and take special process measures during the preparation of the composite material. However, the traditional composite material preparation technology has the following problems: Insufficient interfacial bonding between the fiber and the metal matrix will cause the composite material to fail easily when subjected to external forces, thus affecting the overall performance. The fiber is unevenly distributed in the metal matrix, which will lead to local performance differences in the composite material, thus affecting its consistency and reliability.

[0003] The presence of high residual stress inside the material will affect the long-term stability and service life of the composite material. The grain size is too large. Large grain size will lead to a decrease in the plasticity and toughness of the material, especially in high temperature environments. Summary of the invention

[0004] The object of the present invention is to provide a fiber reinforced metal composite material and a preparation method thereof to solve the problems raised in the above background technology.

[0005] To achieve the above object, the present invention provides the following technical solutions: A fiber-reinforced metal composite material and a preparation method thereof, the composite material comprising: A metal matrix, wherein the metal matrix is ​​selected from aluminum alloy, titanium alloy, magnesium alloy, and nickel-based alloy, and the metal matrix is ​​pretreated to improve its bonding with the fiber; High-strength fiber, the high-strength fiber is surface treated, the surface treatment includes but is not limited to chemical plating, coating or plasma treatment, the high-strength fiber is selected from carbon fiber, boron fiber, glass fiber or a combination thereof, and the high-strength fiber is evenly distributed in the metal matrix to form a multi-scale reinforcement structure.

[0006] Preferably, the metal matrix is ​​pretreated, and the pretreatment includes but is not limited to surface oxidation treatment, chemical etching or physical and mechanical grinding to improve the interface bonding between the metal matrix and the fiber; The surface oxidation treatment is carried out by chemical oxidation in a mixed solution of nitric acid and phosphoric acid at 60° C. to 80° C. for 30 minutes to 60 minutes to form a dense oxide film on the surface of the metal substrate.

[0007] Preferably, the volume fraction of the high-strength fiber in the metal matrix is ​​20% to 40%, preferably 25% to 35%.

[0008] Preferably, the diameter of the high-strength fiber is 5 μm to 20 μm, preferably 7 μm to 15 μm.

[0009] Preferably, the composite material is subjected to heat treatment, wherein the heat treatment comprises annealing at 400° C. to 600° C. for 2 to 4 hours to further optimize the microstructure of the material; The tensile strength of the composite material is not less than 1200 MPa, and the fracture toughness of the composite material is not less than 60 J / m².

[0010] The present invention also protects a method for preparing a fiber-reinforced metal composite material, comprising the following steps: (a) performing surface treatment on the high-strength fiber to improve the interface bonding between the high-strength fiber and the metal matrix, wherein the surface treatment includes but is not limited to chemical plating, coating or plasma treatment, preferably chemical plating technology, wherein the chemical plating includes but is not limited to nickel or copper; (b) immersing the treated high-strength fiber into a molten metal matrix, wherein the temperature of the molten metal matrix is ​​700° C. to 800° C., and a refiner is further added to the molten metal matrix, wherein the refiner is selected from zirconium or magnesium; (c) performing hot pressing at a temperature between 500° C. and 600° C. and a pressure between 10 MPa and 30 MPa, wherein the hot pressing time is between 5 minutes and 15 minutes to ensure uniform distribution of the fibers in the metal matrix; (d) performing post-treatment, including but not limited to annealing at a temperature between 450° C. and 550° C. for a time of 2 hours to 4 hours, wherein the annealing is performed in a vacuum environment to remove residual stress in the material and optimize the microstructure of the material.

[0011] Preferably, in step (a), the surface treatment adopts chemical plating technology, the chemical plating layer includes but is not limited to nickel or copper, and the thickness of the chemical plating layer is 1nm to 10nm, preferably 2nm to 5nm; The chemical plating process comprises the following steps: Nickel sulfate was selected as the coating material, sodium hypophosphite was used as the reducing agent, and sodium citrate was used as the stabilizer; The high-strength fiber is placed in a plating solution containing nickel sulfate, sodium hypophosphite and sodium citrate, and is plated at a pH of 4 to 5 and a temperature of 50°C to 70°C for 30 to 60 minutes to form a nickel plating layer with a thickness of 2nm to 5nm on the fiber surface.

[0012] Preferably, in step (b), a refiner is further added to the molten metal matrix, and the mass percentage of the refiner is 0.1% to 1%, preferably 0.3% to 0.7%.

[0013] Preferably, in step (c), the hot pressing forming further comprises applying lateral vibration during the forming process to further promote uniform distribution of the fibers in the metal matrix.

[0014] Preferably, the composite material further comprises a micro-nano scale particle reinforcement phase, the particle reinforcement phase is selected from aluminum oxide, silicon carbide, silicon nitride or a combination thereof, and the volume fraction of the particle reinforcement phase in the metal matrix is ​​1% to 10%, preferably 2% to 5%.

[0015] The present invention has at least the following beneficial effects: (1) This solution significantly enhances the interfacial bonding between the fiber and the metal matrix through surface treatment (such as chemical plating, plasma treatment, coating treatment, etc.) and appropriate pretreatment methods (such as surface oxidation treatment, chemical etching treatment, etc.), thereby improving the tensile strength and fracture toughness of the composite material. The use of lateral vibration technology effectively promotes the uniform distribution of fibers in the metal matrix and reduces the uneven performance caused by fiber aggregation.

[0016] (2) This solution achieves effective grain refinement of the metal matrix by adding a refiner (such as zirconium Zr), thereby improving the comprehensive mechanical properties of the material; (3) Through special treatment of the fiber surface, reasonable selection of refiners and optimization of the preparation process, this solution enables the tensile strength of the final composite material to reach or exceed 1200MPa and the fracture toughness to reach or exceed 60J / m², while ensuring good distribution of the fibers in the matrix; (4) This scheme adopts annealing treatment to effectively eliminate the residual stress generated in the preparation process of the composite material, optimize the microstructure of the material, and improve its stability and service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0018] Figure 1 The present invention is a flow chart of the preparation method. DETAILED DESCRIPTION

[0019] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] Example 1 See also Figure 1 The present invention provides a technical solution: a fiber reinforced metal composite material metal matrix, the material of the metal matrix is ​​6061 aluminum alloy, pretreatment: surface oxidation treatment, treated in a mixed solution of nitric acid and phosphoric acid at 60°C to 80°C for 45 minutes to form a dense oxide film.

[0021] The material of the high-strength fiber is carbon fiber (CF), diameter: 10μm, volume fraction: 30%, surface treatment: chemical plating technology, the plating material is nickel, and the thickness is about 3nm.

[0022] Among them, the 6061 aluminum alloy is subjected to surface oxidation treatment to form a dense oxide film, which improves the corrosion resistance and oxidation resistance of the metal matrix, and at the same time provides better interface bonding strength for the subsequent bonding of the fiber and the metal matrix.

[0023] A method for preparing a fiber reinforced metal composite material is as follows: Nickel sulfate was selected as the coating material, sodium hypophosphite was used as the reducing agent, and sodium citrate was used as the stabilizer.

[0024] The carbon fiber is chemically plated using nickel sulfate as the coating material, sodium hypophosphite as the reducing agent, and sodium citrate as the stabilizer to form a uniform and highly adhesive nickel coating, thereby improving the interface bonding between the fiber and the metal matrix and thus improving the overall performance of the composite material.

[0025] The carbon fiber was placed in a plating solution containing nickel sulfate, sodium hypophosphite and sodium citrate, and the plating treatment was carried out at a pH value of 4.5 and a temperature of 60°C for 45 minutes.

[0026] The carbon fiber is placed in the plating solution for plating treatment to ensure uniform plating. The plating treatment forms a stable plating layer on the surface of the carbon fiber, which helps to improve the bonding strength between the fiber and the matrix material.

[0027] After treatment, the fiber was washed with deionized water and dried at 80°C for 1 hour. Washing away the residual plating solution and drying can ensure that the fiber surface is clean and free of moisture, which is conducive to subsequent processing.

[0028] The 6061 aluminum alloy is heated to 750°C and 0.5% zirconium (Zr) is added after melting. Heating and melting the aluminum alloy facilitates the subsequent mixing operation. The addition of zirconium can refine the aluminum alloy grains and improve its mechanical properties.

[0029] The coated carbon fiber is immersed in the molten aluminum alloy to ensure that the fibers are evenly distributed. The immersion operation makes the fibers fully contact with the molten aluminum alloy, and the lateral vibration promotes the uniform distribution of the fibers in the aluminum alloy to avoid local concentration or segregation.

[0030] Hot pressing was performed at 550°C and 20 MPa for 10 minutes, and lateral vibration was applied to promote uniform distribution of the fibers. The material was densified under high temperature and high pressure conditions, and lateral vibration further promoted uniform distribution of the fibers, improving the density and uniformity of the composite material.

[0031] Keep the temperature and pressure stable during the molding process.

[0032] The formed composite material was annealed in a vacuum environment at 500°C for 3 hours to remove residual stress in the material and optimize the microstructure.

[0033] After annealing, it is cooled naturally to room temperature.

[0034] In this embodiment, tensile strength: the tensile strength of the test sample is not less than 1200 MPa. Fracture toughness: the fracture toughness of the test sample is not less than 60 J / m². Microstructure analysis: the microstructure of the composite material is observed using a scanning electron microscope (SEM) to confirm the distribution of the fibers in the matrix.

[0035] Example 2 The present invention also protects a technical solution: a fiber-reinforced metal composite material metal matrix, the material of the metal matrix is ​​MgAZ31 magnesium alloy, and the pretreatment is chemical etching treatment.

[0036] The material of the high-strength fiber is glass fiber (GF), diameter: 15μm, volume fraction: 25%, surface treatment: plasma treatment.

[0037] A method for preparing a fiber reinforced metal composite material is as follows: The glass fiber is surface treated by a plasma treatment device to improve the interface bonding between the fiber and the metal matrix.

[0038] The treatment time was 10 minutes using an argon plasma.

[0039] The MgAZ31 magnesium alloy was heated to 720°C and then melted and 0.3% of magnesium (Mg) was added as a refiner.

[0040] The treated glass fibers are dipped into the molten magnesium alloy to ensure even distribution of the fibers.

[0041] Hot pressing was performed at 520 °C and a pressure of 15 MPa for 15 min, and lateral vibration was applied to promote uniform distribution of the fibers.

[0042] The formed composite material was annealed in a vacuum environment at 450°C for 2 hours.

[0043] After annealing, it is cooled naturally to room temperature.

[0044] In this embodiment, tensile strength: whether the tensile strength of the test sample is not less than 1200MPa. Fracture toughness: whether the fracture toughness of the test sample is not less than 60J / m². Microstructure analysis: SEM is used to observe the microstructure of the composite material to confirm the distribution of the fibers in the matrix.

[0045] Example 3 The present invention also protects a technical solution: a fiber-reinforced metal composite material metal matrix, the material of the metal matrix is ​​Ti6Al-4V titanium alloy, and the pretreatment is physical and mechanical grinding.

[0046] The material of the high-strength fiber is boron fiber (BF), diameter: 7μm, volume fraction: 35%, surface treatment: coating treatment.

[0047] A method for preparing a fiber reinforced metal composite material is as follows: The boron fiber is surface treated with a specific coating material to improve the interface bonding between the fiber and the metal matrix.

[0048] The coating material may be a silane coupling agent, such as 3-aminopropyltriethoxysilane (APTES).

[0049] The Ti6Al-4V titanium alloy was heated to 800°C and then melted and 0.7% of zirconium (Zr) was added as a refiner.

[0050] The treated boron fibers are dipped into molten titanium alloy to ensure even distribution of the fibers.

[0051] Hot pressing was performed at 580 °C and a pressure of 25 MPa for 5 min, and lateral vibration was applied to promote uniform distribution of the fibers.

[0052] The formed composite material was annealed in a vacuum environment at 550°C for 4 hours.

[0053] After annealing, it is cooled naturally to room temperature.

[0054] In this embodiment, tensile strength: whether the tensile strength of the test sample is not less than 1200MPa. Fracture toughness: whether the fracture toughness of the test sample is not less than 60J / m². Microstructure analysis: SEM is used to observe the microstructure of the composite material to confirm the distribution of the fibers in the matrix.

[0055] Example 4 The present invention also protects a technical solution: a fiber reinforced metal composite material metal matrix, the material of the metal matrix is ​​Ni-based superalloy, and the pretreatment is surface oxidation treatment.

[0056] The material of the high-strength fiber is carbon fiber (CF), diameter: 5μm, volume fraction: 20%, surface treatment: chemical plating technology, the plating material is copper, and the thickness is about 1nm.

[0057] It also includes a particle reinforcement phase, the particle reinforcement phase material is alumina (Al2O3), volume fraction: 5% A method for preparing a fiber reinforced metal composite material is as follows: Copper sulfate was selected as the coating material, sodium hypophosphite was used as the reducing agent, and sodium citrate was used as the stabilizer.

[0058] The carbon fiber was placed in a plating solution containing copper sulfate, sodium hypophosphite and sodium citrate, and the plating treatment was carried out at a pH value of 4.5 and a temperature of 60°C for 30 minutes.

[0059] After treatment, the fibers were washed with deionized water and dried at 80 °C for 1 h.

[0060] The Ni-based superalloy is heated to 700°C, melted and then 0.1% of zirconium (Zr) as a refiner is added.

[0061] The coated carbon fibers and Al2O3 powder are mixed and immersed in molten nickel-based alloy to ensure uniform distribution of the fibers.

[0062] Hot pressing was performed at 500 °C and a pressure of 10 MPa for 15 min, and lateral vibration was applied to promote uniform distribution of the fibers.

[0063] The formed composite material was annealed in a vacuum environment at 400°C for 2 hours.

[0064] After annealing, it is cooled naturally to room temperature.

[0065] In this embodiment, tensile strength: whether the tensile strength of the test sample is not less than 1200MPa. Fracture toughness: whether the fracture toughness of the test sample is not less than 60J / m². Microstructure analysis: SEM is used to observe the microstructure of the composite material to confirm the distribution of the fibers in the matrix.

[0066] Example 5 The present invention also protects a technical solution: a fiber-reinforced metal composite material metal matrix, the metal matrix material is Inconel 718 nickel-based alloy, pretreatment: surface oxidation treatment. The high-strength fiber material is Kevlar fiber, diameter: 8μm, volume fraction: 30%, surface treatment: chemical plating technology, the plating material is silver, thickness is about 2nm. The particle reinforcement phase material is silicon carbide (SiC), volume fraction: 10%.

[0067] The preparation method is as follows: Metal matrix: The surface of Inconel 718 nickel-based alloy is oxidized in a mixed solution of nitric acid and phosphoric acid at 60°C to 80°C for 45 minutes to form a dense oxide film.

[0068] High-strength fiber: Kevlar fiber surface treatment, using silver for chemical plating, the coating thickness is about 2nm.

[0069] Silver nitrate is used as the coating material, sodium sulfite is used as the reducing agent, and sodium citrate is used as the stabilizer.

[0070] The Kevlar fiber was placed in a plating solution containing silver nitrate, sodium sulfite and sodium citrate, and the coating treatment was carried out at a pH of 4.5 and a temperature of 60°C for 45 minutes. After the treatment, the fiber was washed with deionized water and dried at 80°C for 1 hour. The Inconel 718 nickel-based alloy was heated to 750°C, melted and 0.5% of the refiner titanium (Ti) was added. The plated Kevlar fiber and SiC powder were mixed and immersed in the molten nickel-based alloy to ensure that the fibers and particles were evenly distributed.

[0071] Hot pressing was performed at 550°C and 25 MPa for 10 min, with lateral vibration applied to promote uniform distribution of fibers and particles. The temperature and pressure were kept stable during the molding process.

[0072] The formed composite material was annealed in a vacuum environment at 500°C for 3 hours to remove residual stress in the material and optimize the microstructure. After annealing, it was naturally cooled to room temperature.

[0073] Tensile strength: Test whether the tensile strength of the sample is not less than 1200MPa.

[0074] Fracture toughness: Test whether the fracture toughness of the sample is not less than 60J / m².

[0075] Microstructure Analysis: Scanning electron microscopy (SEM) was used to observe the microstructure of the composites and confirm the distribution of fibers and particles in the matrix.

[0076] Effects of this embodiment: Surface oxidation treatment can enhance the corrosion resistance and wear resistance of the base material; chemical plating treatment improves the interfacial bonding between the fiber and the base. Adding a refiner can refine the grains and improve the mechanical properties of the material; the uniform distribution of fibers and particles can further enhance the comprehensive performance of the material. Molding under high temperature and high pressure ensures the density of the material, and lateral vibration promotes the uniform distribution of fibers and particles. Annealing treatment can eliminate internal stress, optimize the microstructure, and improve the stability and reliability of the material.

[0077] Comparative Example 1 Aluminum alloy based carbon fiber composites without fiber surface treatment The material of the metal matrix is ​​6061 aluminum alloy, and the pretreatment is: surface oxidation treatment, which is treated in a mixed solution of nitric acid and phosphoric acid at 60°C to 80°C for 45 minutes to form a dense oxide film.

[0078] The material of the high-strength fiber is carbon fiber (CF), diameter: 10 μm, volume fraction: 30%, surface treatment: no surface treatment is performed.

[0079] The preparation method is as follows: The 6061 aluminum alloy was heated to 750°C and then melted and 0.5% zirconium (Zr) was added as a refiner.

[0080] The untreated carbon fibers are directly dipped into the molten aluminum alloy to ensure even fiber distribution.

[0081] Hot pressing was performed at 550 °C and a pressure of 20 MPa for 10 min, and lateral vibration was applied to promote uniform distribution of the fibers.

[0082] The formed composite material was annealed in a vacuum environment at 500°C for 3 hours.

[0083] After annealing, it is cooled naturally to room temperature.

[0084] Comparative Example 2 Magnesium alloy-based glass fiber composites without metal matrix pretreatment The material of the metal matrix is ​​MgAZ31 magnesium alloy, and pretreatment: no pretreatment is performed.

[0085] The material of the high-strength fiber is glass fiber (GF), diameter: 15μm, volume fraction: 25%, surface treatment: plasma treatment.

[0086] The preparation method is as follows: The glass fiber is surface treated by a plasma treatment device to improve the interface bonding between the fiber and the metal matrix.

[0087] The treatment time was 10 minutes using an argon plasma.

[0088] The MgAZ31 magnesium alloy was heated to 720°C and then melted and 0.3% of magnesium (Mg) was added as a refiner.

[0089] The treated glass fibers are dipped into the molten magnesium alloy to ensure even distribution of the fibers.

[0090] Hot pressing was performed at 520 °C and a pressure of 15 MPa for 15 min, and lateral vibration was applied to promote uniform distribution of the fibers.

[0091] The formed composite material was annealed in a vacuum environment at 450°C for 2 hours.

[0092] After annealing, it is cooled naturally to room temperature.

[0093] Comparative Example 3 Nickel-based alloy-based carbon fiber composites without adding refiner The material of the metal matrix is ​​Ni-based superalloy, and the pretreatment is surface oxidation treatment.

[0094] The material of the high-strength fiber is carbon fiber (CF), diameter: 5μm, volume fraction: 20%, surface treatment: chemical plating technology, the plating material is copper, and the thickness is about 1nm.

[0095] It also includes a particle reinforcement phase, and the material of the particle reinforcement phase is aluminum oxide (Al2O3) with a volume fraction of 5%.

[0096] The preparation method is as follows: Copper sulfate was selected as the coating material, sodium hypophosphite was used as the reducing agent, and sodium citrate was used as the stabilizer.

[0097] The carbon fiber was placed in a plating solution containing copper sulfate, sodium hypophosphite and sodium citrate, and the plating treatment was carried out at a pH value of 4.5 and a temperature of 60°C for 30 minutes.

[0098] After treatment, the fibers were washed with deionized water and dried at 80 °C for 1 h.

[0099] The Ni-based superalloy is heated to 700°C and melted without adding refiners.

[0100] The coated carbon fibers and Al2O3 powder are mixed and immersed in molten nickel-based alloy to ensure uniform distribution of the fibers.

[0101] Hot pressing was performed at 500 °C and a pressure of 10 MPa for 15 min, and lateral vibration was applied to promote uniform distribution of the fibers.

[0102] The formed composite material was annealed in a vacuum environment at 400°C for 2 hours.

[0103] After annealing, it is cooled naturally to room temperature.

[0104] In summary, the effects of the embodiments and comparative examples are as follows: Example 1: Surface oxidation treatment enhances the corrosion resistance and surface hardness of the aluminum alloy matrix. Chemical plating technology (nickel plating) improves the interfacial bonding strength between the carbon fiber and the aluminum alloy matrix, which helps to improve the mechanical properties of the overall composite material. The addition of zirconium as a refiner refines the aluminum alloy grains, further improving the mechanical properties of the material. Transverse vibration promotes the uniform distribution of fibers in the matrix, avoiding local stress concentration. Annealing eliminates residual stress inside the material, optimizes the microstructure, and improves the overall performance of the material.

[0105] Example 2 Chemical etching treatment improves the surface roughness of the magnesium alloy matrix, which is beneficial to the good bonding of the fiber and the matrix. Plasma treatment improves the interfacial bonding strength between the glass fiber and the magnesium alloy matrix, thereby enhancing the performance of the composite material. The addition of refiner magnesium also helps to refine the grains and improve the strength and toughness of the material. Transverse vibration helps to evenly disperse the fibers in the matrix and reduce the generation of defects. Annealing treatment eliminates the residual stress inside the material and optimizes the microstructure.

[0106] Example 3 Physical and mechanical grinding improves the surface quality of the titanium alloy substrate and enhances the bonding strength between the substrate and the fiber. Coating treatment (such as silane coupling agent) strengthens the interface bonding between the boron fiber and the titanium alloy substrate, which helps to improve the performance of the composite material. The addition of zirconium as a refiner refines the titanium alloy grains and enhances the overall performance of the material. Transverse vibration helps to evenly distribute the fibers in the matrix and improves the consistency of the material. Annealing eliminates residual stress inside the material and optimizes the microstructure.

[0107] Example 4: Surface oxidation treatment improves the corrosion resistance of the nickel-based alloy, chemical plating technology (copper plating) improves the interfacial bonding strength between the carbon fiber and the nickel-based alloy matrix, the addition of zirconium as a refiner helps to refine the grains, further improving the mechanical properties of the material, the particle reinforcement phase improves the hardness and wear resistance of the composite material, lateral vibration promotes the uniform distribution of fibers and particles in the matrix, and annealing eliminates the residual stress inside the material and optimizes the microstructure.

[0108] In Comparative Example 1, the interfacial bonding force between the carbon fibers that have not been surface treated and the aluminum alloy matrix is ​​weak, resulting in the tensile strength and fracture toughness of the material being lower than expected.

[0109] In comparative example 2, the surface roughness of the magnesium alloy substrate that has not been pretreated is insufficient, which may affect the interfacial bonding force between the fiber and the substrate, and further affect the overall performance of the composite material.

[0110] Comparative Example 3 without adding a refiner may result in a larger grain size of the nickel-based alloy, which will reduce the strength and toughness of the composite material, especially the performance at high temperatures.

[0111] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0112] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A fiber-reinforced metal composite material, characterized in that: The composite material comprises: A metal matrix, wherein the metal matrix is ​​selected from aluminum alloy, titanium alloy, magnesium alloy, and nickel-based alloy, and the metal matrix is ​​pretreated to improve its bonding with the fiber; High-strength fiber, the high-strength fiber is surface treated, the surface treatment includes but is not limited to chemical plating, coating or plasma treatment, the high-strength fiber is selected from carbon fiber, boron fiber, glass fiber or a combination thereof, and the high-strength fiber is evenly distributed in the metal matrix to form a multi-scale reinforcement structure.

2. The fiber-reinforced metal composite material according to claim 1, characterized in that: The metal matrix is ​​pretreated, and the pretreatment includes but is not limited to surface oxidation treatment, chemical etching or physical and mechanical grinding to improve the interface bonding between the metal matrix and the fiber; The surface oxidation treatment is carried out by chemical oxidation in a mixed solution of nitric acid and phosphoric acid at 60° C. to 80° C. for 30 minutes to 60 minutes to form a dense oxide film on the surface of the metal substrate.

3. The fiber-reinforced metal composite material according to claim 1, characterized in that: The volume fraction of the high-strength fiber in the metal matrix is ​​20% to 40%.

4. The fiber-reinforced metal composite material according to claim 1, characterized in that: The high-strength fiber has a diameter of 5 μm to 20 μm.

5. The fiber-reinforced metal composite material according to claim 1, characterized in that: The composite material is subjected to heat treatment, wherein the heat treatment includes annealing at 400° C. to 600° C. for 2 to 4 hours to further optimize the microstructure of the material.

6. A method for preparing a fiber reinforced metal composite material according to any one of claims 1 to 5, characterized in that: The following steps are involved: (a) performing surface treatment on the high-strength fiber to improve the interface bonding between the high-strength fiber and the metal matrix, wherein the surface treatment includes but is not limited to chemical plating, coating or plasma treatment; (b) immersing the treated high-strength fiber into a molten metal matrix, wherein the temperature of the molten metal matrix is ​​700° C. to 800° C., and a refiner is further added to the molten metal matrix, wherein the refiner is selected from zirconium or magnesium; (c) performing hot pressing molding at a temperature between 500° C. and 600° C. and a pressure between 10 MPa and 30 MPa, wherein the hot pressing molding time is between 5 minutes and 15 minutes; (d) performing post-treatment, including but not limited to annealing at 450° C. to 550° C. for 2 to 4 hours, wherein the annealing is performed in a vacuum environment.

7. The method for preparing a fiber reinforced metal composite material according to claim 6, characterized in that: In step (a), the surface treatment adopts chemical plating technology, the chemical plating layer includes but is not limited to nickel or copper, and the thickness of the chemical plating layer is 1nm to 10nm, preferably 2nm to 5nm; The chemical plating process comprises the following steps: Nickel sulfate was selected as the coating material, sodium hypophosphite was used as the reducing agent, and sodium citrate was used as the stabilizer; The high-strength fiber is placed in a plating solution containing nickel sulfate, sodium hypophosphite and sodium citrate, and is plated at a pH of 4 to 5 and a temperature of 50°C to 70°C for 30 to 60 minutes to form a nickel plating layer with a thickness of 2nm to 5nm on the fiber surface.

8. The method for preparing a fiber-reinforced metal composite material according to claim 6, characterized in that: In step (b), a refiner is further added to the molten metal matrix, and the mass percentage of the refiner is 0.1% to 1%.

9. The method for preparing a fiber reinforced metal composite material according to claim 6, characterized in that: In step (c), the thermoforming further comprises applying lateral vibration during the forming process.

10. The method for preparing a fiber reinforced metal composite material according to claim 6, characterized in that: The composite material further comprises a micro-nano-scale particle reinforcement phase, wherein the particle reinforcement phase is selected from aluminum oxide, silicon carbide, silicon nitride or a combination thereof, and the volume fraction of the particle reinforcement phase in the metal matrix is ​​1% to 10%.

Citation Information

Cited By

  • High-thermal-conductivity creep-resistant corrosion-resistant composite reinforced core aluminum stranded wire and preparation method thereof

    CN121862506A